Spectrum Watching Implementation on Cognitive Radio - Abbaspour, Reza (My University, 2011)
Modern wireless communication constantly faces RF band shortage especially in commercial applications while all useful bands are already licensed and occupied. Thus, the initiation of new wireless services is not possible because of the critical shortage of free bands. On the other hand, there are only small band potions (ISM band) left for free where the interference level is very high. That is why new technologies are utilized to use the frequency bands efficiently. Cognitive radio is one important and promising technique to reuse the licensed bands, which means that the usage permission of a certain frequency band must not make any harmful interference to the primary (licensed) user and this is accomplished by an accurate spectrum-watching device to decide whether a certain band is free or not. In this project, high-speed spectrum-watching hardware is implemented to be employed in cognitive-radio. However, spectrum-watching device is a generic hardware for different purposes but, the main application is to be used for cognitive radio. Thus the device input is customized to accept RF analog signal from a digital receiver module. The system architecture is designed and implemented in fully hierarchical manner, performing modular approach by allowing the end-user to work with functional blocks in form of daughter boards. In other words, sub-systems are prototyped as distinct modules which can be plugged in together in order to handle the spectrum-watching process. The whole system converts analog signals with maximum 8MHz to digital bit stream and transferring the information via a USB 2.0 connection to PC side for further analysis, which means that the input 8MHz baseband signal can be monitored by a PC. In this regard, RF down-converter module should be configured in a manner that to be compatible with designed spectrum-watching device by properly setting the internal local-oscillator and sweeping circuit. In sum, the thesis highlights the design challenges, system architecture and implementation procedure as well as prototypes’ functionality in order to produce knowledge which might be only maintained and protected by commercial manufacturers that produce high-speed ADCs and data acquisition blocks. In this regard, the project homepage at the following address represents all information as well as source codes and executable files, supporting the project: http://www.abbreza.com/en/spectrum.htm
Keywords: Spectrum-watching; High-speed ADC; PC-based Data Transfer; Cognitive Radio; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|